Real time PCR quantification of goat - defensin mRNA expressed by different tissues of Osmanabadi goat - C, SHENDE TEJAS; K, BARATE ABHIJIT; VIPUL (The Indian Journal of Animal Sciences, 2023)
In the present investigation, goat β-defensin (GBD) expression in different tissues of Osmanabadi goat was studied. Goat tongue epithelia had the highest level of GBD expression, followed by reticulum, rumen, omasum, kidney, spleen, liver and uterus. Minimal expression of GBD was observed in Osmanabadi tracheal tissue. To our knowledge, this is the first study to report expression of GBD in goat rumen.